Pengaruh Konflik Peran Ganda Dan Stres Kerja Terhadap Kinerja Pegawai Di Kementerian Agama Kabupaten Lebak - Eris Harismasakti; Munawati Munawati (E-Journal Studia Manajemen, 2021)
The decline in employee performance is due to the presence of several employees who have multiple roles. When a person faces work stress, their performance will decrease. Work stress on female employees is a woman's response to a condition or event that arises because of the interaction between the woman and other individuals with her job as an employee in a company which can interfere with her physical and psychological condition. The purpose of this study was to determine the influence of multiple role conflicts and job stress on employee performance. The method used in this study is a quantitative method. The hypothesis of this study is that there is a relationship between Multiple Role Conflict and Job Stress on Employee Performance. The population used in this study were 84 employees at the Ministry of Religion in Lebak Regency. The sampling technique used purposive sampling, the sample used was employees who had multiple roles as many as 40 people. The analysis technique used is the prerequisite technique of data analysis, multiple linear regression analysis, the coefficient of determination test, partial test and simultaneous test. Based on data analysis, it can be concluded that partially multiple role conflicts have a significant effect on employee performance, while job stress has no significant effect on employee performance. Simultaneously multiple roles conflict and job stress (independent variable) affect employee performance (dependent variable)